Minigene splicing assessment of 20 novel synonymous and intronic glucokinase gene variants identified in patients with maturity‐onset diabetes of the young. Issue 1 (15th November 2019) - Tiulpakov, Anatoly; Zubkova, Natalia; Makretskaya, Nina; Krasnova, Tatiana S.; Melnikova, Anna I.; Fedyaeva, Alena S.; Vasilyev, Evgeny; Petrov, Vasily M.; Rubtsov, Petr M.
Abstract: The next‐generation sequencing (NGS) has become a routine method for diagnostics of inherited disorders. However, assessment of the discovered variants may be challenging, especially when they are not predicted to change the protein sequence. Here we performed a functional analysis of 20 novel or rare intronic and synonymous glucokinase ( GCK ) gene variants identified by targeted NGS in 1, 130 patients with maturity‐onset diabetes of the young. Human Splicing Finder, ver 3.1 and a precomputed index of splicing variants (SPIDEX) were used for in silico prediction. In vitro effects of GCK gene variants on splicing were tested using a minigene expression approach. In vitro effect on splicing was shown for 9 of 20 variants, including two synonymous substitutions. In silico and in vitro results matched in about 50% of cases. The results demonstrate that novel or rare apparently benign GCK gene variants should be regarded as potential splicing mutations.